Wireless sensor network redundancy node sleep scheduling algorithm - Tao WEN; Dong-qing ZHANG; Quan GUO; Xiao-ying SONG (Tongxin xuebao)
A scheduling algorithm for redundant nodes is proposed to effectively prolong the lifetime of WSN.The algorithm focuses on two problems.One is to prevent a large number of nodes shifting at the same time from working state into sleeping state to avoid the appearance of blind areas,the other is to employ different scheduling strategies on border nodes and internal nodes to avoid contraction of the network boundary by judging whether a node is on the network boundary according to the number of working nodes in its neighbor table.The simulation results show that the algorithm can effectively prolong the lifetime of WSN.